Environmental Sustainability Analysis of L-Tryptophan as a Consumer Product and Intermediate to Pharmaceutical Active Ingredients - Overcash, Alan; Griffing, Evan; Sukumara, Sumesh; Overcash, Michael (Frontiers in Sustainability, 2022)
L-tryptophan is a naturally occurring α-amino acid that is also purchased by consumers for medicinal and dietary purposes. L-tryptophan is also a starting point for synthesizing medical derivatives with antiplatelet aggregation and antibacterial activity. Beneficial direct use and subsequent synthetic product use were evaluated with respect to the environmental footprint of the cradle-to-L-tryptophan manufacturing process, using the next generation life cycle inventory technology of the Environmental Genome. The principal route is fermentation from sugar (dextrose). The environmental metrics quantified were natural resource energy combustion (NREc) and CO2eq for air (defined below). The environmental boundary includes 137 chemical intermediates (gate-to-gates, gtg), of which 33 are non-repeating, with the most consequential for the environmental metrics being dextrose and the L-tryptophan. The cradle-to-gate process energy is 147 MJ/kg L-tryptophan, while the more comprehensive natural resource energy combustion (NREc) is 222 MJ/kg L-tryptophan. The carbon footprint is 18.7 kg CO2equivalent /kg L-tryptophan, with 53% of this from the cradle-to-gate of the supply chains. It is important to note this is only a partial environmental assessment of L-tryptophan since the environmental benefits of use in consumption and when used to make preventative pharmaceuticals are not included.